The relationships between loneliness, social identity and sensation-seeking with the tendency towards virtual social networks - Karim , sevari (International Journal of Psychosocial Rehabilitation, 2020)
The present study investigated the relationships between loneliness, social identity and sensation-seeking with the tendency towards social networks. The population consisted of all students in Ahvaz Payam Noor University, from where173 participants were selected voluntarily. The research design was correlation, and regression was used for data analysis. Data were collected using Russell, Pella and Katrona’s (1980)Loneliness questionnaire, Social Identity questionnaire of Jenkines(2008), a researcher-made Sensation- seeking questionnaire (2017), and a researcher-made Virtual Social Networks questionnaire (2018).The results of the study demonstrated that sensation-seeking positively predicted the tendency towards social networks; however, social identity and loneliness negatively did it. In addition, loneliness, sensation-seeking and social identity played the most important roles in predicting the tendency towards social networks.